The Routledge handbook of religion and secrecy - Urban, Hugh B.; Johnson, Paul Christopher (Routledge handbooks in religion, 2022)
Introduction: From the Social Lives of Secrecy to the Secret lives of the Social: Notes on Religion, Power, and the Public Paul Christopher Johnson and Hugh B. UrbanPart 1: Configurations of Religious Secrecy: Conceptual and Comparative Frameworks1. Mysticism and Secrecy Arthur Versluis2. Esotericism and Secrecy Kennet Granholm3. Gender, Sexuality, and Secrecy Hugh B. Urban4. Psychedelics and Secrecy Christopher Partridge5. Architectures of Secrecy Paul Christopher Johnson6. Secrecy, the Paranormal, and the Imaginal: The Remote Viewing Literature Jeffrey J. Kripal and Christopher SennPart 2: Secrecy as Religious Practice 7. Secrecy in Islam, Sufism, and Shi'ism Mark Sedgwick8. Concealing the Concealment: Towards a Theopolitics of Kabbalistic Esotericism Elliot R. Wolfson9. Keeping Secrets: The Social Practice of Gnostic Secrecy April D. DeConick10. Secrecy's Situational Ironies: Hiding and Its Consequences for Covert Buddhists in Japan Clark Chilson11. Notions of Secrecy and the Unknown/ Hidden in Chinese Religions Barend ter Haar12. Secrecy in South Asian Hindu Traditions: The Gods Love What is Occult Gordan Djurdjevic13. Reflections on Secrecy in Yolngu Religion Ian Keen14. AWO: The Nature of Secrecy in YoruÌbaì Religious Traditions: Conversations with Ifa Diviners Jacob K. OluponaPart 3: Secrecy and the Politics of the Present 15. Secrecy and Freemasonry Henrik Bogdan16. The Sacred, the Secret, and the Sinister in the Latter-day Saint Tradition Christopher James Blythe17. The High Magic of Jesus Christ: Materializing Secrets in Brazil's Valley of the Dawn Kelly E. Hayes18. Secrecy, Sex Abuse, and The Practice of Priesthood John C. Seitz19. From Resistance to Terror: The Open Secret of Jonestown Rebecca MoorePart 4: Secrecy and Social Resistance20. Crypto-Paganism in the Late Antique World: Models of Concealment in a Christian Empire, Fourth to Sixth Century CE David Frankfurter21. Hopi Knowledge and the Ethnographic Allure of Secrets Adam Fulton Johnson22. Secrecy, Spirit Work, and Women's Fugitive Speech in the Creolophone Caribbean Elizabeth McAlister23. Lifting the EucharisticVeil: Allan Rohan Crite as Afro-Anglican Mystagogue Hugh R. Page, Jr. and Stephen C. FinleyPart 5: Secrecy, Terrorism, and Surveillance24. Weaponizing Secrecy: The FBI's War on Black Radical Religion Sylvester Johnson25. Varieties of Secrecy and Symbolism in American White Power Movements Damon Berry26. The Islamic State and the Management of Secrecy Haroro J. Ingram and Craig Whiteside27. Conspiracy Theories about Secret Religions: Imagining the Other David G. Robertson28. Xenophobia and Conspiracism after 9/11 Michael Barkun29. Imagining Secret Wars Mark Juergensmeyer.Index